A Qualitative Study of MSMEs Perception and Practices towards Islamic Finance in Rural Areas - Romadhani, Aoktavia Taniatul (Journal of Banks and Financial Institutions, 2025)
Objective: This study aims to explore the perceptions and practices of micro, small, and medium enterprises (MSMEs) in rural areas regarding Islamic finance, highlighting the gap between ideal perceptions and actual practices. Research Design & Methods: A qualitative phenomenological approach was used to capture the lived experiences of MSME actors MSMEs in adopting Islamic finance. Data was collected through in-depth interviews and thematic analysis was used to identify patterns and challenges. Findings: The findings reveal significant differences between positive perceptions of Islamic finance and its practical implementation. Although most respondents expressed strong support for Sharia principles— valuing fairness, interest-free systems, and alignment with religious values — its implementation is hindered by limited access to Islamic financial institutions, complex administrative procedures, and a lack of knowledge about available Shariah-based financial products. The study also highlights the potential of Islamic fintech and government support as key drivers for overcoming these barriers. Implications & Recommendations: This study shows that improving financial literacy, simplifying administrative processes, expanding access to Islamic financial services in rural areas, and utilizing fintech innovations can significantly increase MSME participation in Islamic finance. Stronger policy support and targeted programs for rural MSMEs are recommended to strengthen the Islamic financial ecosystem. Contribution & Value Added:  This study contributes to the literature by providing empirical insights into the perception-practice gap among rural SMEs in adopting Islamic finance. It highlights the interplay between religious values, structural constraints, and technological opportunities, and offers practical recommendations for policymakers, financial institutions, and technology providers to promote inclusive Islamic finance.